(3HMhK aj GdEJUGd (B/s - (3hgHj, SMQ eMeOs ((3GdbGgQI (B:s (3OGQ GdaLQ ddfTQ h GdJhRjY ,s, 2002)
(3jTed gPG GdcJGH SHY OQGSGJ efgG OQGSI JJYdb HeLGd JCKjQ hSGFd GdEYdGe Ydi bWGY YQjV ef GdLeghQ h gh bWGY WdGH GdLGeYI GdQcjRI GdGhdi ddJfejI h Ced GdHdGO h eSJbHdgGs
(3HHdjhZQGajG (B: (3U(B.360-361s
Keywords: (3GdEYdGes; (3GdUMa GdeUQjIs; (3hSGFd GdEYdGes; (3GdGJUGds